Resistance to Fluoroquinolones in Pseudomonas aeruginosa from Human, Animal, Food and Environmental Origin: The Role of CrpP and Mobilizable ICEs - María López; Beatriz Rojo-Bezares; Gabriela Chichón; Yolanda Sáenz (MDPI AG, 2022)
Fluoroquinolone resistance and the associated genetic mechanisms were assessed by antimicrobial susceptibility and whole genome sequencing in 56 Pseudomonas aeruginosa strains from human, animal, food and environmental origins. P. aeruginosa PAO1, PA7 and PA14 reference strains were also included in the study. Twenty-two strains (37%) were resistant to, at least, one fluoroquinolone agent. Correlation between the number of changes in GyrA and ParC proteins and the level of fluoroquinolone resistance was observed. Mutations or absence of genes, such as mexZ, mvaT and nalD encoding efflux pumps regulators, were also found in resistant strains. The crpP gene was detected in 43 strains (72.9%; 17 of them non-clinical strains), and coded seven different CrpP variants, including a novel one (CrpP-7). The crpP gene was located in 23 different chromosomal mobile integrative and conjugative elements (ICEs), inserted in two tRNAs integration sites. A great variety of structures was detected in the crpP-ICEs elements, e.g., the fimbriae related cup clusters, the mercury resistance mer operon, the pyocin S5 or S8 bacteriocin encoding genes, and mobilization genes. The location of crpP-like genes in mobilizable ICEs and linked to heavy metal resistance and virulence factors is of significant concern in P. aeruginosa. This work provides a genetic explanation of the fluoroquinolone resistance and crpP-associated pathogenesis of P. aeruginosa from a One-Health approach.